2021
DOI: 10.1007/s10666-021-09784-4
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Effects of Trade Openness in the Presence of Structural Breaks: New Insights from 5-ASEAN Developing Countries

Abstract: A number of studies have investigated the environmental consequences of international trade. However, they have neglected comprehensively exploring the trade-environment nexus in the presence of structural breaks. This paper attempts to empirically analyse the effect of trade openness on carbon dioxide emissions and nitrous oxide emissions as proxies of environmental degradation in five ASEAN developing countries individually, namely, Vietnam, Thailand, Malaysia, Indonesia, and the Philippines. The Clemente-Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…This idea leads to the hypotheses of the pollution halo and pollution haven through the EKC. According to Tran and Do (2021), trade openness and FDI caused environmental degradation in Malaysia and Indonesia in the long term but not in Thailand. Le et al (2016) found that trade openness impacted positively in high-income countries, but had a negative impact in low and middle income countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This idea leads to the hypotheses of the pollution halo and pollution haven through the EKC. According to Tran and Do (2021), trade openness and FDI caused environmental degradation in Malaysia and Indonesia in the long term but not in Thailand. Le et al (2016) found that trade openness impacted positively in high-income countries, but had a negative impact in low and middle income countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Trade openness and FDI in a country where investment circulates will influence the whole ecosystem (Le et al. , 2016; Oktavilia and Firmansyah, 2016; Tran and Do, 2021). This idea leads to the hypotheses of the pollution halo and pollution haven through the EKC.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation